Effects of Dairy Product Consumption on Height and Bone Mineral Content in Children: A Systematic Review of Controlled Trials. (15th May 2019) - de Lamas, Carmela; de Castro, María José; Gil-Campos, Mercedes; Gil, Ángel; Couce, María Luz; Leis, Rosaura
ABSTRACT: There is a physiological basis for the roles of selected nutrients, especially proteins, calcium, and vitamin D, in growth and development, which are at a maximum during the pediatric period. Milk and dairy products are particularly rich in this group of nutrients. The present systematic review summarizes the available evidence relating dairy product intake with linear growth and bone mineral content in childhood and adolescence. A search was conducted in the MEDLINE (via PubMed) and SCOPUS databases following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and included intervention-controlled clinical trials with dairy products in children from 1 January, 1926 to 30 June, 2018. The risk of bias for each study was assessed using the Cochrane methodology. The number of study participants, the type of study and doses, the major outcomes, and the key results of the 13 articles included in the review are reported. The present systematic review shows that supplementing the usual diet with dairy products significantly increases bone mineral content during childhood. However, the results regarding a possible relation between dairy product consumption and linear growth are inconclusive.